Influence of urban greenery on thermal comfort: a case study in a tropical city - Araujo, Myrella Katlhen da Cunha de; Bastos, Keila Diovana Oliveira; Antunes, Arlindo Modesto (Revista Nacional de Gerenciamento de Cidades, 2023)
This case study focused on the city of São Luís (MA), aiming to analyze the role of urban greenery in the thermal comfort of São Luís, identifying urban and landscape planning strategies that promote the integration of urban vegetation to create a more livable and thermally comfortable environment in the city. To do so, a research methodology with an exploratory and quantitative-qualitative character was employed, involving data collection on temperature and precipitation provided by INMET, as well as a floristic survey in the central region of São Luís, considering the significant impact of urban vegetation on the city's temperature and precipitation. The results showed a strong association between the urbanization process and the increase in urban temperatures, a phenomenon known as the "urban heat island," while urban greenery has been proven as an effective strategy to mitigate this effect, even under conditions aggravated by the El Niño phenomenon. In this context, the research also revealed that an increase in urban vegetation can have positive impacts on reducing temperature and improving the thermal comfort of residents, with the analysis of climate data from 2018 to 2023 being crucial in understanding the relationship between urban vegetation and thermal conditions in the city. The results emphasize the importance of the quantitative-qualitative approach, which allows for a comprehensive and in-depth analysis of the studied phenomenon. Furthermore, the use of climate data provides a solid foundation for analysis and encourages the exploration of specific urban and landscape planning strategies, taking into consideration the effectiveness of these strategies in enhancing thermal comfort within urban centers.